Controlling WC/Co two-phase microstructure of cemented carbides additive-manufactured by laser powder bed fusion: Effect of powder composition and post heat-treatment. (15th November 2021) - Ibe, Hiroyuki; Kato, Yuta; Yamada, Junya; Kato, Masaki; Suzuki, Asuka; Takata, Naoki; Kobashi, Makoto
Graphical abstract: Highlights: The as-fabricated WC-Co microstructures were characterized by two types regions. Heat-treatment homogenizes the heterogeneous microstructure of as-fabricated WC-Co. Co and C of heat-treated LPBF samples reduced by laser irradiation. The C addition to the WC-17Co affected the constituent phases after heat treatment. Co and W3 Co3 C phase area fractions in heat-treated samples affect Vickers hardness. Abstract: In this study, an attempt is made to control the WC-Co two-phase microstructures by laser powder-bed fusion (LPBF) process using cemented carbide powders with different compositions of WC-25Co (mass%) and WC-17Co (mass%) and post heat-treatment at 1380 °C. The as-built cemented carbide samples had different microstructures from those of the cemented carbides fabricated by conventional manufacturing methods. The microstructures of the as-fabricated WC-25Co and WC-17Co cemented carbides were characterized by two types of regions. Region 1 consisted of W2 C and W3 Co3 C phases, including numerous pores and defects. Region 2 consisted of WC and Co phases. Post heat-treatment of the LPBF-built WC-25Co sample at 1380 °C led to the formation of a defect-free WC-Co two-phase microstructure. In contrast, the W3 Co3 C phase remained in the LPBF-built WC-17Co sample even after heat treatment. The addition of carbon to the WC-17Co powder prevented the formation of the W3 Co3 C phase in the cemented carbide processed by LPBF and subsequent heat treatments. The addition of carbon to the WC-17Co powder had a slight effect on the hardness of as-fabricated samples, but reduced the hardness of heat-treated samples. The reduced hardness was attributed to the increased volume fractions of the WC and W3 Co3 C phases.